IMPACT OF TOP MANAGEMENT TEAM HETEROGENEITY ON CORPORATE VALUE IN CHINESE LISTED COMPANIES: THE MODERATING EFFECT OF EXECUTIVE SHAREHOLDING AND OWNERSHIP CONCENTRATION - Shen, Ning; He, Xiaoming; Zhuo, Zhiyi (วารสารปัญญาภิวัฒน์, 2020)
In the era of innovation and development in China, top management team (TMT) plays an increasingly important role in corporate value. Based on the Upper Echelons Perspective Theory, this paper explores the direct impact of top management team heterogeneity on corporate value, and verifies the moderating role of executive shareholding and ownership concentration. Based on the empirical analysis of 6597 panel data of Chinese listed companies from 2010-2014, this paper finds that the TMT tenure heterogeneity and TMT functional experience heterogeneity are positively correlated with corporate value, while the TMT educational level heterogeneity is negatively correlated with corporate value. Also, there is a very interesting discovery: executive shareholding and ownership concentration did not strengthen the positive impact of TMT heterogeneity on corporate value, but strengthened the negative significant impact of TMT educational level heterogeneity on corporate value. The results of the study provide a very meaningful practical reference for corporate governance in Chinese listed companies.